No effects of different doses of New Zealand blackcurrant extract on cardiovascular responses during rest and submaximal exercise across a week in trained male cyclists - Montanari, S.; Sahin, M. A.; Lee, B. J.; Blacker, S. D.; Willems, M. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Supplementation with anthocyanin-rich blackcurrant increases blood flow, cardiac output, and stroke volume at rest. It is not known whether cardiovascular responses can be replicated over longer timeframes in fed trained cyclists. In a randomized, double-blind, crossover design, 13 male trained cyclists (age 39 ± 10 years, VO2max 55.3 ± 6.7 ml·kg-1·min-1) consumed two doses of New Zealand blackcurrant (NZBC) extract (300 and 600 mg/day for 1 week). Cardiovascular parameters were measured during rest and submaximal cycling (65% VO2max) on day 1 (D1), D4, and D7. Data were analyzed with an RM ANOVA using dose (placebo vs. 300 vs. 600 mg/day) by time point (D1, D4, and D7). Outcomes from placebo were averaged to determine the coefficient of variation within our experimental model, and 95% confidence interval (CI) was examined for differences between placebo and NZBC. There were no differences in cardiovascular responses at rest between conditions and between days. During submaximal exercise, no positive changes were observed on D1 and D4 after consuming NZBC extract. On D7, intake of 600 mg increased stroke volume (3.08 ml, 95% CI [-2.08, 8.26]; d = 0.16, p = .21), cardiac output (0.39 L/min, 95% CI [-1.39, .60]; d = 0.14, p = .40) (both +2.5%), and lowered total peripheral resistance by 6.5% (-0.46 mmHg·min/ml, 95% CI [-1.80, .89]; d = 0.18, p = .46). However, these changes were trivial and fell within the coefficient of variation of our study design. Therefore, we can conclude that NZBC extract was not effective in enhancing cardiovascular function during rest and submaximal exercise in endurance-trained fed cyclists.